1988
DOI: 10.1177/089686088800800408
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Cystic Disease of the Kidney in Continuous Ambulatory Peritoneal Dialysis (CAPD) Patients

Abstract: Acquired Cystic Disease of the Kidney (ACDK) has been increasingly noted in patients with long-standing renal failure and in those treated with dialysis. We assessed the prevalence of different patterns of cysts in 48 randomly selected patients treated with CAPD (23.1 ± 16.0 months). Only 3 patients had been previously treated with hemodialysis. All patients underwent renal ultrasonography (US) and nine underwent computerized tomography (CT). In 22 patients no cysts were found. The other 24 patients were Inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Both male and female patients may develop ACKD. While some investigators reported no gender difference (7, 17, 21), others showed a definite male predominance (10,24,25,(28)(29)(30). Variable patient selection criteria account for these differences.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Both male and female patients may develop ACKD. While some investigators reported no gender difference (7, 17, 21), others showed a definite male predominance (10,24,25,(28)(29)(30). Variable patient selection criteria account for these differences.…”
Section: Prevalencementioning
confidence: 99%
“…It has been claimed that blacks have a greater tendency to develop ACKD than whites (21), yet other studies failed to show this (22, 31), and few reports of ACKD specify the race of patients studied. Patients on chronic peritoneal dialysis were reported to develop ACKD less frequently than patients on hemodialysis ( 18, 24), but subsequent reports showed no difference in prevalence of ACKD (7,27,30,35,36).…”
Section: Prevalencementioning
confidence: 99%